2015
DOI: 10.5455/jice.20150313021918
|View full text |Cite
|
Sign up to set email alerts
|

Medicinal plants with potential anti-arthritic activity:

Abstract: Ethno Pharmacological Relevance: Traditional medicinal plants are practiced worldwide for treatment of arthritis especially in developing countries where resources are meager. This review presents the plants profiles inhabiting throughout the world regarding their traditional usage by various tribes/ethnic groups for treatment of arthritis.Materials and Methods:Bibliographic investigation was carried out by analyzing classical text books and peer reviewed papers, consulting worldwide accepted scientific databa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
67
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 132 publications
(79 citation statements)
references
References 209 publications
0
67
0
Order By: Relevance
“…The methanolic extract of G. glabra rhizomes, at a dose of 150 mg/kg, has antiarthritic activity in male rats by inhibition of leukocyte migration, autoantigen production, and exhibition of antiproteinase activity (Choudhary, Kumar, Malhotra, & Singh, ). Also, Mishra, Bstia, Mishra, Chowdary, and Patra () reported that a combined formulation of G. glabra and Boswellia serrata (1:1) had a significant synergistic action on arthritis.…”
Section: Pharmacological Propertiesmentioning
confidence: 99%
“…The methanolic extract of G. glabra rhizomes, at a dose of 150 mg/kg, has antiarthritic activity in male rats by inhibition of leukocyte migration, autoantigen production, and exhibition of antiproteinase activity (Choudhary, Kumar, Malhotra, & Singh, ). Also, Mishra, Bstia, Mishra, Chowdary, and Patra () reported that a combined formulation of G. glabra and Boswellia serrata (1:1) had a significant synergistic action on arthritis.…”
Section: Pharmacological Propertiesmentioning
confidence: 99%
“…On the other hand, drug-resistant bacterial strains have been creating serious treatment issues; therefore, the search for new antimicrobial substances effective against resistant pathogenic microorganisms to conventional antibiotic treatments is necessary. Natural resources have been exploited in the last years, and plant compounds could be an alternative source of new or at least coadjutant treatment (9).…”
Section: Introductionmentioning
confidence: 99%
“…Inject phenytoin intraperitoneally to a group of 4-5 rats. Wait for 0.5 h and subject the animals to electroconvulsions as described earlier 12,13 .…”
Section: Introduction Experimentalmentioning
confidence: 99%